The Negative Effect of Preexisting Immunity on Influenza Vaccine Responses Transcends the Impact of Vaccine Formulation Type and Vaccination History - Moritzky, Savannah A; Richards, Katherine A; Glover, Maryah A; Krammer, Florian; Chaves, Francisco A; Topham, David J; Branche, Angela; Nayak, Jennifer L; Sant, Andrea J (The Journal of infectious diseases, 2023)
Abstract The most effective measure to induce protection from influenza is vaccination. Thus, yearly vaccination is recommended, which, together with infections, establishes diverse repertoires of B cells, antibodies, and T cells. We examined the impact of this accumulated immunity on human responses in adults to split, subunit, and recombinant protein-based influenza vaccines. Enzyme-linked immunosorbent assay (ELISA) assays, to quantify serum antibodies, and peptide-stimulated CD4 T-cell cytokine ELISpots revealed that preexisting levels of hemagglutinin (HA)-specific antibodies were negatively associated with gains in antibody postvaccination, while preexisting levels of CD4 T cells were negatively correlated with vaccine-induced expansion of CD4 T cells. These patterns were seen independently of the vaccine formulation administered and the subjects’ influenza vaccine history. Thus, although memory CD4 T cells and serum antibodies consist of components that can enhance vaccine responses, on balance, the accumulated immunity specific for influenza A H1 and H3 proteins is associated with diminished future responses. The impact of accumulated influenza-specific antibodies and CD4 T cells on human responses to influenza vaccines was examined. These studies revealed that, on balance, preexisting immunity specific for influenza A H1 and H3 proteins is associated with diminished future responses.